1994
DOI: 10.1002/jmv.1890430218
|View full text |Cite
|
Sign up to set email alerts
|

Variability of polymerase chain reaction‐based detection of human papillomavirus DNA is associated with the composition of vaginal microbial flora

Abstract: The results of repeated human papillomavirus (HPV) DNA testing were compared to changes in cervical pathology and the composition of vaginal microorganisms. A cohort of 19 women with HPV cervical infections in the absence of cervical intraepithelial neoplasia at enrollment was reexamined on average at 7.3-month intervals over a 2-year period. At each follow-up visit, cytological and colposcopic examinations were done and vaginal microorganisms were assessed quantitatively by Gram staining of secretions, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
2
29
0
1
Order By: Relevance
“…Cervical inflammation has been proposed as 1 of the cofactors in cervical carcinogenesis since disturbance of the vaginal flora is known to increase the risk of acquisition of HPV infection. 1,[25][26][27] This is consistent with the general hypothesis that the local cervicovaginal milieu plays a role in susceptibility to HPV infection. In this context we ought to remark that it is not possible in the KOPAC system to code simultaneously for koilocytosis and dysbacteriosis or Gardnerella.…”
Section: Discussionsupporting
confidence: 78%
“…Cervical inflammation has been proposed as 1 of the cofactors in cervical carcinogenesis since disturbance of the vaginal flora is known to increase the risk of acquisition of HPV infection. 1,[25][26][27] This is consistent with the general hypothesis that the local cervicovaginal milieu plays a role in susceptibility to HPV infection. In this context we ought to remark that it is not possible in the KOPAC system to code simultaneously for koilocytosis and dysbacteriosis or Gardnerella.…”
Section: Discussionsupporting
confidence: 78%
“…Cervical inflammation has been proposed as one of the cofactors in cervical carcinogenesis, because it has been established that disturbance of the vaginal flora increases the risk acquiring HPV infection. [25][26][27][28] Papanicolaou and Traut 29 and Mead 30 previously confirmed that women with cervical carcinoma often had a dysbacteriotic flora, lacking the normally protective lactobacilli. In the current study, we also noted that women with dysbacteriosis in their smears had a significantly but slightly greater risk of developing (pre)neoplastic changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported in part by other studies that investigated women with dysbacteriosis. 15,17,25,31,32 However, 2 studies showed similar frequencies of dysbacteriosis among women who had squamous intraepithelial lesions (SIL) compared with women who did not have SIL. 33,34 This discrepancy may be explained by the finding that the data in these studies were gathered simultaneously instead of over time.…”
Section: Discussionmentioning
confidence: 99%
“…Typical symptoms include an abnormal vaginal discharge or a fishy odor after sex (owing to the volatilization of the bacterial amines in the presence of the high-pH semen); however, many cases of bacterial vaginosis are asymptomatic. BV is associated with an increased risk for many serious upper genital tract problems, including pelvic inflammatory disease and cervical intraepithelial neoplasia (McNicol, Paraskevas, & Guijon, 1994;Paavonen et al, 1987). Pregnant women with BV are at increased risk for preterm birth, amniotic fluid infection, and endometritis (Hillier et al, 1988;Gravett, Hummel, Eschen-bach, & Holmes, 1986;Holst, Goffeng, & Andersch, 1994).…”
Section: Introductionmentioning
confidence: 99%